2014
DOI: 10.5194/acp-14-13681-2014
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oxidation of 1,3-butadiene: characterization of gas and aerosol reaction products and implications for PM<sub>2.5</sub>

Abstract: Abstract. Secondary organic aerosol (SOA) was generated by irradiating 1,3-butadiene (13BD) in the presence of H 2 O 2 or NO x . Experiments were conducted in a smog chamber operated in either flow or batch mode. A filter/denuder sampling system was used for simultaneously collecting gasand particle-phase products. The chemical composition of the gas phase and SOA was analyzed using derivativebased methods (BSTFA, BSTFA + PFBHA, or DNPH) followed by gas chromatography-mass spectrometry (GC-MS) or high-performa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 79 publications
(126 reference statements)
2
20
0
1
Order By: Relevance
“…This could represent a substituent effect that influences the sensitivity of the gas-phase precursors to reaction by the acidic sulfate nucleophile, but further organic analysis of the aerosol-phase constituents would be required to examine this possibility in detail. Although recent studies have compared the reaction pathways and products formed for 1,3-butadiene oxidation vs. isoprene oxidation (Jaoui et al, 2014), these studies did not focus on acid-influenced reactions or organosulfate formation. Table 4 provides the initial conditions for the two isoprene/NO experiments designed to examine changes in SOC formation and yields resulting from changes in humidity.…”
Section: -Butadiene Acidity Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…This could represent a substituent effect that influences the sensitivity of the gas-phase precursors to reaction by the acidic sulfate nucleophile, but further organic analysis of the aerosol-phase constituents would be required to examine this possibility in detail. Although recent studies have compared the reaction pathways and products formed for 1,3-butadiene oxidation vs. isoprene oxidation (Jaoui et al, 2014), these studies did not focus on acid-influenced reactions or organosulfate formation. Table 4 provides the initial conditions for the two isoprene/NO experiments designed to examine changes in SOC formation and yields resulting from changes in humidity.…”
Section: -Butadiene Acidity Variationmentioning
confidence: 99%
“…With respect to aerosol formation, 1,3-butadiene is also of interest as a structural analog for isoprene. SOA formation from 1,3-butadiene has been examined in a number of recent studies (Angove at al., 2006;Sato, 2008;Sato et al, 2011;Jaoui et al, 2014), although with only limited consideration of the effects of aerosol acidity.…”
Section: Lewandowski Et Al: Atmospheric Oxidation Of Isoprene Andmentioning
confidence: 99%
“…For instance, malic acid and tartaric acid were found in aged wood smoke in oxidation experiments (Hartikainen et al, 2020). However, they can be produced in the oxidation of 1,3-butadinene and isoprene (Claeys et al, 2004;Jaoui et al, 2014). Malic acid can also be produced by the hydroxylation of succinic acid, an oxidation product of long-chain unsaturated fatty acids (Kawamura et al, 1996;Kawamura and Ikushima, 1993).…”
Section: Clustering Of Compounds By Hcamentioning
confidence: 99%
“…In addition, there is evidence for the importance of chlorine atom reactions with various alkanes and alkyl nitrates in the arctic troposphere during springtime [9,10]. 1,3-butadiene, and 2,3-dimethyl-2butene among those VOC emitted into the troposphere principally from many sources like fuel combustion and from refinery industry and biomass burning as well as many other sources of burning and forest fires [11,12]. However, the reactions of 1,3-Butadiene in the troposphere with OH radicals, NO 3 radicals, and O 3 can participate in the removal processes of 1,3-Butadiene from this layer.…”
Section: Introductionmentioning
confidence: 99%
“…Because of OH high concentrations, its reaction with 1,3-Butadiene dominates in the atmosphere during the daytime, while the loss processes through the reactions with ozone and NO 3 still doing its part in the overall removal process of 1,3-Butadiene from the atmosphere. Acrolein and formaldehyde have been noticed as the initial products from those reactions and considerably furan from the reaction with OH, and nitrates from the reaction with NO 3 [5,11]. There were some studies suggested that a possible reaction of 2,3-dimethyl 2butene with bromine may be participated in elimination of this compound from the atmosphere [13].…”
Section: Introductionmentioning
confidence: 99%